Tyrosinase Inhibition Activity and Phytochemical Screening of Melaleuca leucadendron L. Leaves - Munawarohthus Sholikha; Ainun Wulandari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Melaleuca leucadendron L. is a plant whose almost all parts (bark, leaves, twigs, and fruit) can be used as medicine, such as antioxidants, antifungals, sedative effects, and anti-hyaluronidase. This research was conducted to determine tyrosinase inhibition activity and compound content of M. leucadendron leaves. Maceration of M. leucadendron leaves was done in methanol, then carried out liquid-liquid fractionation with n-butanol, chloroform, and water. Methanol extract, butanol fraction, chloroform fraction, and water fraction were tested for phytochemical screening and tyrosinase inhibition using L-DOPA substrate with an ELISA plate well reader. The results of the tyrosinase inhibition activity test at concentrations of 100, 1000 and 10000 μg/mL respectively showed that methanol extract 29.532%, 55.227%, 89.583%; butanol fraction 29.313%, 59.174%, 94.737%, chloroform fraction 21.820%, 24.671%; 53.765%; water fraction 24,086%, 47.661%, 91.118%. Inhibition of the tyrosinase enzyme is shown through the IC50 value from methanol extract, butanol fraction and water fraction, and kojic acid as a positive control, respectively 645.438 μg/mL, 517.935 μg/mL, 669.403 μg/mL, 50.064 μg/mL. Phytochemical screening showed that the extract and fraction contained tannins, flavonoids, saponins, terpenes, and steroids. These results indicate that the butanol fraction is more potent as an anti-tyrosinase agent than the others.